Portugal : Report on the Observance of Standards and Codes-Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2003)
This report provides an assessment of fiscal transparency practices in Portugal against the requirements of the IMF Code of Good Practices on Fiscal Transparency. IMF staff observed that Portugal meets the requirements of fiscal transparency code in several areas. Significant progress has also been made in strengthening fiscal management and transparency at all levels of government. However, in the view of IMF staff, further corrective efforts are required on the part of Portuguese policymakers. They recommend a monitoring unit be set up in all public-private partnership projects and state-owned enterprise (SOE) activities.